Taxonomic review of the genus Dusungwua Kemal, Kizildağ & Koçak, 2020 (Lepidoptera: Pyralidae), with descriptions of six new species and propositions of synonyms - Ren, Yingdang; Yang, Linlin; Liu, Hongxia; Li, Houhun (Zootaxa, 2020)
Eleven species of the genus Dusungwua Kemal, Kizildağ & Koçak 2020 in China are reviewed with emendation of the generic charaters. Among them, six new species, Dusungwua antennalveata Ren & Li, sp. nov., D. basinigra Ren & Li, sp. nov., D. fascecornuta Ren & Li, sp. nov., D. paripalpa Ren & Li, sp. nov., D. similiquadrangula Ren & Li, sp. nov. and D. strictivinculum Ren & Li, sp. nov. are described as new to science. Also, the following taxonomic changes are proposed: Eurhodope pseudodichromella Yamanaka, 1980 syn. nov. is synonymized with D. dichromella (Ragonot, 1893), Trachycera nipponella Yamanaka, 2000 syn. nov., Trachycera vicinella Yamanaka, 2000 syn. nov. and Trachycera yakushimensis Yamanaka, 2000 syn. nov. are synonymized with D. paradichromella (Yamanaka, 1980). The female of D. quadrangula (Du, Sung & Wu, 2005) is described for the first time. Photos of adults as well as male and female genitalia are provided, along with a key to the Chinese species and a distibution map to show the localities of these species.